2021
DOI: 10.1111/ppa.13415
|View full text |Cite
|
Sign up to set email alerts
|

Volatile compounds from plum genotypes with different levels of resistance to leaf scald disease

Abstract: Plum leaf scald (PLS) is the main obstacle to plum expansion in Brazil. This disease is caused by Xylella fastidiosa, which colonizes the foregut of xylem‐sap feeding insects and the xylem of the plants. Breeding programmes identified new plum genotypes that showed no leaf scald symptoms in the field and remained negative for X. fastidiosa for at least 10 years. However, the mechanisms that confer this resistance are not fully elucidated. One hypothesis is the emission of volatile organic compounds by the host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…The experimental results of this study showed that the fractions of Nanocnide lobata extracted using petroleum ether, ethyl acetate, n-butanol and water mainly contain volatile oils, coumarins, lactones, phenolic tannins, steroids, triterpenoids, reducing sugars, polysaccharides and glycosides, phenolic tannins, amino acids, polypeptides and proteins, and organic acid compounds. Similar to our results, it has been reported that volatile oils may have a beneficial effect on the healing of burns and scalds [24,25]; reducing sugars may also be beneficial for burns and scalds [26]. In addition, phenolic tannins and phenolic compounds have been reported to have a significant curative effect on burns and scalds, which is consistent with our results [27].…”
Section: Plos Onesupporting
confidence: 93%
“…The experimental results of this study showed that the fractions of Nanocnide lobata extracted using petroleum ether, ethyl acetate, n-butanol and water mainly contain volatile oils, coumarins, lactones, phenolic tannins, steroids, triterpenoids, reducing sugars, polysaccharides and glycosides, phenolic tannins, amino acids, polypeptides and proteins, and organic acid compounds. Similar to our results, it has been reported that volatile oils may have a beneficial effect on the healing of burns and scalds [24,25]; reducing sugars may also be beneficial for burns and scalds [26]. In addition, phenolic tannins and phenolic compounds have been reported to have a significant curative effect on burns and scalds, which is consistent with our results [27].…”
Section: Plos Onesupporting
confidence: 93%